Redesain Struktur Organisasi untuk Efektivitas Layanan Kesehatan Mental: Studi Kualitatif di Rumah Sakit Jiwa Provinsi Bali - Yasa, Sang Made Agus Wira Nugraha; Thalia, Thalia; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Green Publisher Indonesia, 2025)
This study aims to provide an in-depth analysis of the application of organizational structure theory within the context of public organizations, using a case study of the Provincial Mental Hospital of Bali. The research focuses on how organizational design, authority distribution systems, and both formal and informal power dynamics influence coordination effectiveness and the quality of mental health services. A qualitative descriptive approach with an intrinsic case study method was employed. Data were collected through document analysis, non-participant observation, and semi-structured interviews with five key informants from various managerial levels. The findings reveal that the organization’s classical bureaucratic structure, characterized by five hierarchical layers, tends to hinder decision-making processes and cause fragmentation in inter-unit collaboration. Moreover, informal power dynamics were found to often override formal command lines, thereby disrupting organizational cohesion and reducing operational effectiveness. Based on these findings, the study recommends a redesign of the organizational structure to be more adaptive, decentralized, and collaborative, in order to improve service performance—particularly in the mental health sector, which demands rapid response and a holistic approach. These results not only offer theoretical contributions to the development of public organization theory but also serve as a practical reference for institutional reform in mental health services at both local and national levels.